Pilot study for the registry of complications in rheumatic diseases from the German Society of Surgery (DGORh): evaluation of methods and data from the first 1000 patients. Issue 10 (10th October 2017) - Kostuj, Tanja; Rehart, Stefan; Matta-Hurtado, Ronald; Biehl, Christoph; Willburger, Roland E; Schmidt, Klaus
Abstract : Objective: Most patients suffering with rheumatic diseases who undergo surgical treatment are receiving immune-modulating therapy. To determine whether these medications affect their outcomes a national registry was established in Germany by the German Society of Surgery (DGORh). Data from the first 1000 patients were used in a pilot study to identify relevant corisk factors and to determine whether such a registry is suitable for developing accurate and relevant recommendations. Design and participants: Data were collected from patients undergoing surgical treatments with their written consent. A second consent form was used, if complications occurred. During this pilot study, in order to obtain a quicker overview, risk factors were considered only in patients with complications. Only descriptive statistical analysis was employed in this pilot study due to limited number of observed complications and inhomogeneous data regarding the surgery and the medications the patients received. Analytical statistics will be performed to confirm the results in a future outcome study. Results: Complications occurred in 26 patients and were distributed equally among the different types of surgeries. Twenty one of these patients were receiving immune-modulating therapy at the time, while five were not. Infections were observed in 2.3% of patients receiving and in 5.1% not receiving immunosuppression. Conclusions: Due to the low number of cases, inhomogeneity in the diseases and the treatments received by the patients in this pilot study, it is not possible to develop standardised best-practice recommendations to optimise their care. Based on this observation we conclude that in order to be suitable to develop accurate and relevant recommendations a national registry must include the most important and relevant variables that impact the care and outcomes of these patients.